Exploring tranquility: Eastern and Western perspectives - Christoffersen, Vincent Ringgaard; Škodlar, Borut; Henriksen, Mads Gram (Frontiers in Psychology, 2022)
Despite being a fundamental aspect of human life, experiences of tranquility have gained almost no attention in contemporary research. By contrast, many philosophical, religious, spiritual, or mystical traditions in East and West have strived to reach tranquil states and produced texts serving as manuals to reach them. Yet, no attempt has been made to compare experiences of tranquility and explore what they may have in common. The purpose of this study was to explore the experiential nature of tranquility. We conducted a non-systematic literature search, covering articles in more than 100 journals and numerous books, and identified 47 concepts of tranquil states. Most of these concepts could be sorted into one or more of the following categories: the body, emotions, the mind, and mysticism. We present paradigmatic examples of tranquil states from each of these categories. Finally, we propose that the different tranquil states seem to share specific experiential features, and we offer an exploratory account of tranquility. We suggest that the shared features pertain both to the content or quality of the tranquil states, which involves a sense of presence and inner peace, and to these states’ experiential structure, which seems to involve some degree of detachment and absorption.